RT - PCR과 RFLP법을 이용한 국내 소 로타바이러스 VP4 및 VP7 유전자의 특성 규명 - 전성진; 장정호; 정정원; 김원용; 강신영 (Journal of bacteriology and virology, 1998)
Characterizations of the VP4 (P type) and VP7 (G type) genes of Korean isolates of bovine rotavirus were performed using RT-PCR/RFLP and nucleotide sequencing analysis. After RT- PCR amplification of partial length (1094bp) of the VP4 and full length (1062bp) of the VP7 genes, amplified PCR products were digested with restriction endonucleases and digestion pattems were compared with those of reference rotaviruses. With the VP4 genes, four RFLP (A- D) profiles were observed; three (A, B and C) were the same as those of bovine rotavirus NCDV (P[1]), IND (P[5]) and B223 (P[11]), respectively. Profile D was the same as that of porcine rotavirus OSU (P[7]). With the VP7 genes, five RFLP profiles (I-V) were observed; three of them (I, II and III) were the same as those of bovine rotavirus NCDV (G6), Cody I-801 (G8), and B223 (G10), respectively. Profile IV and V were atypical to those of reference bovine rotaviruses used in this study. These two profiles were identified as G6 and GS, respectively, after analyzing and comparing the nucleotide sequences. The G typing analysis revealed that 61.9% (26/42) were G6, which included G6 subtype; 28.6% (12/42) were G5; 7.1% (3/42) were G10; 2.4% (1/42) were G8. The P typing analysis revealed that 54.S% (23/42) were P[5]; 28.6% (12/42) were P[7]; 11.8% (5/42) were P[11]; 4.8% (2/42) were P[1]. Our results showed that G6/P[5] were the most prevalent rotaviruses in diarrheic calves in Korea. Also, this is the first report that GS/P[7] rotaviruses were identified from cattle with diarrhea.